Predictors of respiratory failure after thoracic surgery: a retrospective cohort study with comparison between lobar and sub-lobar resection - Aldo Pezzuto; Beatrice Trabalza Marinucci; Alberto Ricci; Massimo Ciccozzi; Giuseppe Tonini; Michela D’Ascanio; Giulio Guerrieri; Maria Chianese; Silvia Castelli; Erino Angelo Rendina (Journal of International Medical Research, 2022)
Objective Only approximately 15% of patients with lung cancer are suitable for surgery and clinical postoperative outcomes vary. The aim of this study was to investigate variables associated with post-surgery respiratory failure in this patient cohort. Methods Patients who underwent surgery for lung cancer were retrospectively studied for respiratory function. All patients had undergone lung resection by a mini-thoracotomy approach. The study population was divided into two subgroups for comparison: lobectomy group, who underwent lobar resection; and sub-lobar resection group. Results A total of 85 patients were included, with a prevalence of lung cancer stage IA and adenocarcinoma histotype. Lobectomy (versus sub-lobar resection), the presence of chronic obstructive pulmonary disease (COPD), and a COPD assessment test (CAT) score >10, were all associated with an increased risk of respiratory failure. The partial pressure of arterial oxygen decreased more in the lobectomy group than in the sub-lobar resection group following surgery, with a significant postoperative between-group difference in values. Postoperative CAT scores were also better in the sub-lobar resection group. Conclusions Post-surgical variations in functional parameters were greater in the group treated by lobectomy. COPD, high CAT score and surgery type were associated with postoperative development of respiratory failure.